Effect of Silica Powder to Frost Resistance of Concrete. Issue 3 (May 2019) - Liu, Yanjie; Ding, Lin; Yang, Tianyu; Wang, Xunan
Abstract: The improving strength of concrete is the hot issue. The concrete with silica powder was studied. This experimental study comprises 3 groups concrete specimens with a fixed water/cement ratio. The concrete using various silica powder had improved the concrete relative dynamic elastic modulus and weight loss rate. The experiments showed that the concretes with mixture of silica powder showed good performance, and the concrete frost resistance increased significantly. The silica powder improved its structure of concrete. The tests proposed that silicon powder has great impact.